Analisis Pemahaman Konsep Klasifikasi Makhluk Hidup Peserta Didik Kelas VI SD Negeri 14 Manado - Sumampouw, Zoya; Najoan, Roet; Bella, Miranda C. S.; Kolomban, Deyby (Peneliti.net, 2023)
Biology is one of the materials of science. Biology as a science subject has different principles from other science subjects. It has many concepts contained in biology. One of the complex biological materials found in biology that is difficult for students to understand is material about the classification of living things. Apart from that, the material on the classification of living things generally uses terms that are difficult for students to understand. Therefore, it is necessary to identify concepts in the material for the classification of living things that students have not or have not understood. This research aims to analyze the understanding of the concept of classification of living things in class VI students at SD Negeri 14 Manado. This type of research is descriptive research. The sample was taken using a simple random sampling technique, with a total of 48 students. This research was carried out by giving multiple choice test questions with open reasoning. Data was analyzed quantitatively. The results of the research showed that class VI students at SD Negeri 14 Manado experienced a level of understanding of concepts in the low category. Low understanding of concepts includes concepts about the characteristics of living things 41.66%; basic classification of living things 25.00%; 12.50% determination of key concepts; monera and protista group 16.93%; characteristics of Kingdom Fungi 21.88%; Kingdom Plantae features 20.83%; the difference between mosses, ferns and seed plants is 18.23%; characteristics of Kingdom Animalia 9.38% and differences between Vertebrate and Invertebrate animals 16.02